Crown Witnesses in Indonesian Criminal Procedure: A Critical Review of Legal Status and Legitimacy - Syofia Marlianti Tambunan (LifeSciFi, 2025)
This study investigates the legal status and legitimacy of crown witnesses in the Indonesian criminal justice system a practice still widely used despite lacking explicit legal foundation in the Criminal Procedure Code. The study aims to evaluate whether the crown witness practices aligning with procedural and human rights principles embedded in the Criminal Procedure Code and international law. Using normative legal research with statutory and conceptual approaches, this study analyzes the inconsistency between crown witness practices and Articles 185 and 189 of the Criminal Procedure Code, which clearly differentiate between the roles of witnesses and defendants. Findings reveal that this practice undermines legal certainty, violates the principle of non-self-incrimination in the International Covenant on Civil and Political Rights, and creates a conflict of interest for defendants testifying under oath in related cases. The study concludes that the justice collaborator framework recognized in Supreme Court Circular Number 4/2011 and Law Number 31/2014 offers a more legitimate alternative. It recommends formal codification of witness cooperation in the Criminal Procedure Code reform to uphold fair trial guarantees.